Weak boson fusion at 100 TeV - Gonçalves, Dorival; Plehn, Tilman; Thompson, Jennifer M. (Arxiv, 2017)
From the LHC runs we know that, with increasing collider energy, weak-boson-fusion Higgs production dominates as an environment for precision measurements. We show how a future hadron collider performs for three challenging benchmark signatures. Because all of these measurements rely on the tagging jet signature, we first give a comprehensive analysis of weak-boson-fusion kinematics and a proposed two-step jet veto at a 100 TeV hadron collider. We then find this machine to be sensitive to invisible Higgs branching ratios of 0.5%, a second-generation muon Yukawa coupling of 2%, and an enhanced total Higgs width of around 5%, the latter with essentially no model dependence. This kind of performance crucially relies on a sufficient detector coverage and a dedicated weak-boson-fusion trigger channel.
Gesehen am 10.08.2017